2007
DOI: 10.4028/www.scientific.net/kem.329.687
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Stone Sawing with Thin and Normal Blades

Abstract: In this paper, an experimental study was conducted to compare the sawing of granite with thin and normal blades. The power drawn by the spindle and horizontal and vertical forces were measured. The width of sawing slot on the granite was examined after sawing. For both blades, power and forces increase with the depth of cut. The width of sawing slots for the thin blade was about 75% of the normal blade. The width of sawing slots for either thin or normal blade sawing became narrower in larger depth of cut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…From a technological point of view, a reduction of the thickness of the grinding wheel would be an effective way to achieve this object [1]. In our recent study, an experiment was conducted to compare the sawing with thin and normal blades [2]. It was found that thin sawing could be well done with the sawblade of reduced thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a technological point of view, a reduction of the thickness of the grinding wheel would be an effective way to achieve this object [1]. In our recent study, an experiment was conducted to compare the sawing with thin and normal blades [2]. It was found that thin sawing could be well done with the sawblade of reduced thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a few previous studies tried to grind granite at speeds higher than traditionally used. Denkena et al increased the grinding speeds up to 50m/s in order to cut granite with thin discs [2]. Ersoy et al studied the cutting of different rocks with diamond saws of normal thickness at a constant speed of 65m/s [3].…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde kayaçların fiziko-mekanik özelliklerine bağlı olarak dairesel testerelerde oluşan kesme kuvveti, spesifik enerji ve soketlerin modellenmesi [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], teorik talaş geometrilerinin tanımlanması [24], teğetsel kesme kuvveti ile talaş kalınlığı arasındaki bağıntılar, spesifik kesme enerjisinin belirlenmesi ve güç tüketimi [25], takım aşınması üzerine işleme parametrelerinin etkisi [26], elmas kesici takımlarla doğal taş kesme üzerine bir modelleme [27,28] ve tarama mikroskobu altında talaş örneklerinin spesifik öğütme enerjisi ile ilişkilendirilmesi [29] konularında çalışmalar yapılmıştır. Doğal taş sektöründe yaygın olarak kullanılmaya başlayan karbür kaplı parmak freze uçlar ile kayaçların CNC makinesinde işlenebilirliğini etkileyen parametreler üzerine yapılan çalışmalar oldukça az ve kısıtlıdır.…”
Section: Introductionunclassified
“…Mermerlerin kesilebilirliği ele alındığında; dairesel testerelerde soketlerin modellenmesi kesme kuvvetlerinin saptanması, özgül kesme enerji konularında aşağıdaki araştırmacıların çalışmalarıyla karşılaşılacaktır (Akdaş ve Yurdakul 2014;Aslantaş et al 2009;Bayram et al 2002;Bayram 2013;Büyüksağiş vd. 2003;Ersoy ve Atıcı 2004;2005;Han et al 2007;Hu et al 2006;Karakurt et al 2013;Tönshoff et al 2002;Turchetta 2009;Ucun et al 2011;2012;Yilmazkaya ve Özçelik 2015;Yurdakul ve Akdaş 2012;Yu et al 2006;Xu et al 2003;Wang et al 2004). Bu çalışmalara ilave olarak; Asche etal.…”
Section: Introductionunclassified